The level of safety culture beliefs and practices amongst Safety and Health Officers (SHOS) in Malaysian manufacturing companies - Sirat, R. M. (IEOM Society, 2016)
The objectives of this study are to identify the level of safety culture in terms of the perceptions of the beliefs on the importance at workplace (SCB) and the existing safety culture practice (ESCP), to find out the level of SCB, and to identify to what extend safety is being closely practiced (ESCP) amongst Safety and Health Officers (SHOs). A questionnaire was sent to 173 SHOs in Malaysian manufacturing companies and 146 questionnaires were successfully returned. 22 questions related to self-regulations, commitment, motivation and communication which were identified through literature. Each respondent needs to rate his or her level of understanding of SCB and ESCP. Mean score analysis was used to determine the level of understanding of SCB and ESCP. Subsequently the differences between the two components are shown in a radar graph. The details of the items in identifying the levels of SCB and ESCP were analyzed. The study found the level of SCB is between medium high to high. However, the result of the ESCP shows they were in the range of medium low and high medium level. It is important to identify the level of safety practice in which it will portray the current safety culture in Malaysia especially when it involves ergonomics. This is to make a good strategy to implement ergonomics to inculcate safety culture.